2021
DOI: 10.1016/j.scitotenv.2020.141727
|View full text |Cite
|
Sign up to set email alerts
|

On the linkage between urban heat island and urban pollution island: Three-decade literature review towards a conceptual framework

Abstract: With the doubling of urban population within the next two decades and the disproportionate growth of megacities, it is critical to explore the synergism between urban heat and pollution. In this paper, a systematic review is conducted on the existing knowledge, collected since 1990, on the link between urban heat island (UHI) and urban pollution island (UPI). Results from 16 countries and 11 Köppen-Geiger climatic zones are perused and compared to delineate methodological and experimental trends, geographical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
94
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(103 citation statements)
references
References 197 publications
(362 reference statements)
2
94
0
7
Order By: Relevance
“…Researchers in different fields are trying to find a solution to the urban heat island intensity (UHII) and air pollutant concentrations [7][8][9][10]. Part of the results indicate that there is a close coupling effect between the UHII and urban air pollutant concentrations, which has been confirmed by relevant research [11][12][13]. For instance, Estournel et al [14] found out that the temperature of urban and rural areas in Toulouse varies with the aerosol based on the results of solar radiation.…”
Section: Introductionmentioning
confidence: 92%
“…Researchers in different fields are trying to find a solution to the urban heat island intensity (UHII) and air pollutant concentrations [7][8][9][10]. Part of the results indicate that there is a close coupling effect between the UHII and urban air pollutant concentrations, which has been confirmed by relevant research [11][12][13]. For instance, Estournel et al [14] found out that the temperature of urban and rural areas in Toulouse varies with the aerosol based on the results of solar radiation.…”
Section: Introductionmentioning
confidence: 92%
“…Therefore, we excluded this station from analyses of the relationships between land-use type and air pollutant concentration. At local scale, anthropogenic activities and their urban distribution play an important role for urban pollution [26]. Junk et al [50] indicated that land use and its interaction with other factors can influence air quality.…”
Section: Land-use Types and Major Air Pollutantsmentioning
confidence: 99%
“…Additionally, temperature [22], relative humidity [23], wind direction [24], temperature inversion [25], and so on are related to dispersion and transformation of air pollutants. On the other hand, the intricate feedback loop between urban heat island, temperature-driven chemistry and urban pollution, urbanization also plays an important role for the air quality [26]. Land cover [27], high population density [28], and heavy traffic [29] all can affect pollutants' concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…While the repercussions of urban overheating are multifaceted and naturally diverse, they can be subtly grouped into three broad categories: (I) direct impact on urban dwellers in terms of exerted thermal stress, especially in the summertime or periods of extreme heat events and which results in increased heat-related thermal discomfort, mortalities, and morbidities ( Founda and Santamouris, 2017 ; He et al., 2021 ; Ngarambe et al., 2020 ), (II) heightened urban air pollution levels resulting from synergistic interactions between UHI-related elevated temperatures and atmospheric pollutants often fueled by complex photochemical processes ( Cao et al., 2016 ; Ngarambe et al., 2021 ; Ulpiani, 2021 ), and (III) a serious impact on the energy demand of cities; they increase the cooling load and partially decrease the heating load ( Li et al., 2019 ; Santamouris, 2014 ).…”
Section: Introductionmentioning
confidence: 99%